Gambaran Status Gizi Pasien Pra dan Pascabedah di RS. Dr. Sardjito, Yogyakarta - Widiyanti, Rahayu; Effendy, Christantie; Akhmadi, Akhmadi (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2006)
Please refer to the file